Photosynthetic capacity, photochemical efficiency and chlorophyll content of three varieties of Labisia pumila Benth. Exposed to open field and greenhouse growing conditions. - Jaafar, Hawa Z. E.; Ibrahim, Mohd Hafiz (Springer Link, 2011)
Three varieties (Alata, Pumila and Lanceolata) of Malaysian indigenous medicinal herb Labisia pumila Benth. grown in greenhouse and open field were tested to evaluate and compare their photosynthetic and maximal quantum efficiency of photosystem II (F v/F m) reactions. Every variety grown in greenhouse demonstrated higher light-saturated photosynthetic capacity than in the open field. The diurnal net photosynthesis (A) curve in the open field also displayed dual peaks with lower daily average A compared to the greenhouse. Varieties Alata and Pumila were found to acclimatize better under both growing conditions. The diurnal patterns of F v/F m indicated that plants grown under greenhouse encountered less photoinhibition than in open field condition. A decrease in chlorophyll (chl) a/b ratio in leaves of greenhouse plants with significant increase in chl b was observed. This study indicates that var. Alata and var. Pumila have the capacity to acclimatize to greenhouse growth condition.